2020
DOI: 10.7150/jca.42498
|View full text |Cite
|
Sign up to set email alerts
|

Epstein barr virus encodes miRNAs to assist host immune escape

Abstract: Epstein-barr virus (EBV) is a definite tumorigenic virus, which can form lifelong latency in the host, which is difficult to be recognized and completely eliminated by the immune system. It is closely related to the occurrence and development of nasopharyngeal cancer, gastric cancer and various types of lymphoma. At present, a total of 44 Epstein-barr virus-encoded microRNAs (EBV miRNAs) have been found. In response to the immune system of the body, EBV miRNAs can inhibit the expression and presentation of vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 91 publications
3
14
0
Order By: Relevance
“…A closer look at the literature shows that there is a network of identified EBV-encoded miRNAs and their regulated targets. The identified target genes are mainly located in adaptive and innate immunity and immune escape mechanisms (Albanese et al, 2017), what also corroborates our hypothesis that miRNAs interfere with type I IFN signaling as part of the innate immune escape during EBV infection (Gallo et al, 2020;Iizasa et al, 2020;Li et al, 2020). With our experiments shown in Figures 3 and 4 and documented in Supplementary Figures 3 and 4, we confirmed a number of host cell transcripts targeted by viral miRNAs, but we also identified several previously unknown effectors and their cellular transcripts (Fig.…”
Section: Discussionsupporting
confidence: 88%
“…A closer look at the literature shows that there is a network of identified EBV-encoded miRNAs and their regulated targets. The identified target genes are mainly located in adaptive and innate immunity and immune escape mechanisms (Albanese et al, 2017), what also corroborates our hypothesis that miRNAs interfere with type I IFN signaling as part of the innate immune escape during EBV infection (Gallo et al, 2020;Iizasa et al, 2020;Li et al, 2020). With our experiments shown in Figures 3 and 4 and documented in Supplementary Figures 3 and 4, we confirmed a number of host cell transcripts targeted by viral miRNAs, but we also identified several previously unknown effectors and their cellular transcripts (Fig.…”
Section: Discussionsupporting
confidence: 88%
“…MiRNAs play very important roles in modulating the immune response during viral infections. MiRNAs can repress gene expression by targeting host cellular RNAs or viral RNAs during infection 13‐15 . Furthermore, miRNAs have essential functions in a number of immune‐related diseases 11,18 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, altered expression levels of miRNAs are also associated with various diseases 10,12 . Strikingly, recent studies have shown that miRNAs, as vital modulators, are also involved in the regulation of viral infection and host defense 13‐15 . For instance, previous data suggest that specific miRNAs in hepatitis B virus are associated with liver disease and that Epstein‐Barr virus‐encoded miRNAs collaborate to assist in host immune escape 13‐15 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Particular attention is paid to miR-BART5-3p, and miR-BART1-5p in EBVaGC [ 79 ], since they were found to bind and facilitate degradation of the important tumor suppressor P53 mRNA [ 80 ]. Besides, miR-BART1-5 and miR-BART9 are involved in cell growth and migration by inducing the reduction of important proteins like E-cadherin, which are necessary to maintain epithelial cell cohesion [ 81 , 82 ].…”
Section: Ebv Latency and Epigenetic Activitymentioning
confidence: 99%